The Prognostic Potential of Atrial Natriuretic Peptide on the Development of Postoperative Atrial Fibrillation after Cardiac Surgery - Hofer, Felix; Hammer, Andreas; Steininger, Matthias; Kazem, Niema; Koller, Lorenz; Steinlechner, Barbara; Laufer, Günther; Andreas, Martin; Marculescu, Rodrig; Hengstenberg, Christian; Wojta, Johann; Niessner, Alexander; Sulzgruber, Patrick (Thrombosis and Haemostasis, 2021)
Background Postoperative atrial fibrillation (POAF) represents a common complication after cardiac surgery associated with major adverse events and poor patient outcome. Tools for risk stratification of this arrhythmia remain scarce. Atrial natriuretic peptide (ANP) represents an easily assessable biomarker picturing atrial function and strain; however, its prognostic potential on the development of POAF has not been investigated so far.Methods Within the present investigation, 314 patients undergoing elective cardiac surgery were prospectively enrolled. Preoperative mid-region proANP (MR-proANP) values were assessed before the surgical intervention. Patients were followed prospectively and continuously screened for the development of arrhythmic events.Results A total of 138 individuals (43.9%) developed POAF. Median concentrations of MR-proANP were significantly higher within the POAF group (p < 0.001). MR-proANP showed a strong association with the development of POAF with a crude odds ratio (OR) of 1.68 per 1 standard deviation (1-SD; 95% confidence interval [CI]: 1.31–2.15; p < 0.001), which remained stable after comprehensive adjustment for confounders with an adjusted OR of 1.74 per 1-SD (95% CI: 1.17–2.58; p = 0.006). The discriminatory power of MR-proANP for the development of POAF was validated by the category-free net reclassification improvement (0.23 [95% CI: 0.0349–0.4193]; p = 0.022) and integrated discrimination increment (0.02 [95% CI: 0.0046–0.0397], p = 0.013).Conclusion MR-proANP proved to be a strong and independent predictor of the development of POAF. Considering a personalized diagnostic and prognostic preoperative work-up, a standardized preoperative evaluation of MR-proANP levels might help to identify patients at risk for development of POAF after cardiac surgery.
Keywords: atrial-natriuretic peptide; postoperative atrial fibrillation; cardiac surgery; risk prediction